Reproductive Aspects of Epilepsy - Johnson,MR; Craig,J (Oxford University Press, 2012)
Part of the Oxford Textbooks in Clinical Neurology (OTCN) series, this volume covers the scientific basis, clinical diagnosis, and treatment of the reproductive aspects of epilepsy.